REGULARITIES OF LONG-TERM AND INTERSEASONAL DYNAMICS OF THE CTENOPHORE MNEMIOPSIS LEIDYI POPULATION IN THE CASPIAN SEA - A. M. Kamakin; V. F. Zaitsev (Юг России: экология, развитие, 2014)
Results of long-term (2001-2011) monitoring investigations into the distribution of invader Mnemiopsis leidyi population in all major sea areas through the whole year (January-November) are presented. The scenario of invader Mnemiopsis leidyi development is considered and the further development of its population in the Northern, Middle and Southern Caspian is predicted. Materials presented make it possible to forecast the impact of that gelatinous predator on the main trophic levels of the Caspian Sea ecosystem.